Analisis Finansial Usahatani Padi Varietas Unggul di Desa Guntung Ujung Kecamatan Gambut Kabupaten Banjar Kalimantan Selatan - Adi Syafruwardi; Hairin Fajerin; Hamdani Hamdani (Universitas Lambung Mangkurat, 2012)
The purposes of study are to determine the financial condition on high yield varieties (HYV) rice farming, to know how its feasibility, and find out the farmer problems in the study area. Guntung Ujung Village was selected purposively and the samples were selected by proportioned random sampling based on the rice varieties grown by farmers. Those consist of: 18 farmers of Ciherang, 7 farmers of Siam Saba and 5 farmers of IR-66. The result showed that profit rate for Siam Saba variety was 100.3%, followed by Ciherang and IR-66 with 98% and 47%, respectively. Compared with inflation rate 0.28%, all HYVs were financially feasible since profit rates were higher than inflation rate.